Karakteristik keluarga yang berhubungan dengan status gizi balita umur 6- 59 bulan - Purwanti, Rachma; Wati, Erna Kusuma; Rahardjo, Setiyowati (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2016)
Background: Nutrition is a factor that most determines the quality of human resources. Lack of nutrition during infancy can lead delayed in physical growth, motor development and impaired cognitive development. Family characteristics holds an important role to solve nutrition problems.Objective: to determine the family characteristics associated with nutritional status of children at the Community Health Centers of Sumbang II, Banyumas Regency. Methods: This type of study is a case - control. Sample cases were children aged 6-59 months who have undernutrition status, while the controls were well nourished children aged 6-59 months. Sample of cases and controls each of 46. Data was analyzed using univariate, bivariate, and multivariate methods. Result: Based on this research, it is known that the characteristics of the families studied, which are associated with nutritional status of children in the Community Health Center II Sumbang, Banyumas Regency is the level of mother’s nutritional knowledge with a p value=0.002 and OR=3.875. Other variable of family characteristics, namely large families, health care utilization, and environmental sanitation were not associated with nutritional status of children (p=0.921; p=0.173; p=0.204). Conclusion: Level of mother’s nutritional knowledge was associated with nutritional status. As a suggestion, to improve nutritional status on children at the Community Health Centers of Sumbang II it need to increase knowledge of mothers by training and counseling, better supervision and monitoring of nutritional status of children, and increase roles of an integrated services post.